Mitigating the effects of extreme low-flow on stream macroinvertebrates: the role of woody riparian vegetation and groundwater - Hannah-Marie Stappert; Philipp Blanke; Daniel Hering; Jochem Kail (Hydrobiologia, 2025)
We investigated the role of woody riparian vegetation (WRV) in reducing the detrimental effects of extreme low-flow conditions on macroinvertebrate communities in Central European streams. We hypothesized that WRV decreases water temperature, thereby lessening the impacts of drought on streams. The study was conducted in the Lippe catchment in northwestern Germany at 26 study sections during the summer drought of 2022. Water temperature and macroinvertebrate communities were analyzed. WRV cover, groundwater influx, cross-section form and flow velocity were considered as predictors in structural equation models. We investigated how the immediate effects of extreme summer low-flow on water temperature and macroinvertebrates were mitigated by the four predictors. Shading by WRV and groundwater influx caused a significantly lower mean daily maximum water temperature of 6.6 °C and 4.8 °C, leading to a higher share of stream-type specific and temperature-sensitive macroinvertebrate taxa and feeding types typical for rhithral stream reaches. These results indicate that both WRV and groundwater influx play a crucial role in regulating stream temperature and maintaining stream-type specific macroinvertebrate communities under extreme low-flow conditions. The study highlights WRV management as a key tool for protecting stream ecosystems from the increasing frequency of droughts and related low-flow due to climate change.